Analisis Manajemen Program Bimbingan dan Konseling Kelompok di SMPN 1 Cijulang - Siti Maryam; Dede Ilman Nurzaman; Devi Sri Rahayu; Zulfa Nurlaila (J-STAF: Siddiq, Tabligh, Amanah, Fathonah, 2024)
This research aims to analyze the management of the group guidance and counseling program implemented at SMPN 1 Cijulang. The research method used is a descriptive method with a qualitative approach. Data collection techniques in research are observation, interviews and documentation methods. The results of the research show that the group guidance management carried out at the planning stage was quite effective so that group guidance services could be implemented appropriately. Through activities that are spiritually enhancing, such as congregational Duha prayers and Al-Qur'an study, it turns out to be effective in supporting student learning. This is because most students who have entered secondary school very rarely participate in Koran recitation activities. The teachers also said that students who began diligently participating in recitations and duha prayers regularly at school had a significant impact on the learning process.